Faktor yang Berpengaruh Terhadap Kinerja Sistem Irigasi di Wilayah Semi Arid Pulau Timor melalui Pendekatan Principal Component Analysis - Ida Nurwiana (Jurnal Irigasi, 2019)
Irrigation system is very complex aspects, including irrigation water, irrigation area, the physical infrastructure of irrigation, human resources, irrigation institutional, management, financing, and technology which are interrelated to support agriculture. To increase agricultural production, the efforts made need to be formulated by considering the performance of the irrigation system and the influence of each related factor. This study aims to analyze the factors that influence of performance of the irrigation systems the irrigation area of district/municipality, province, central government in the semi-arid regions of Timor Island through the Principal Component Analysis (PCA) approach. Principal component analysis method uses fifteen indicators from 345 irrigation areas. This study concludes that fifteen variables showed a significant relationship both positive and negative towards the performance of the irrigation systems. The order of the biggest contribution of influences affecting the performance of the irrigation system in the main model component is the institutional aspects of the authority of the district/municipality irrigation area, productivity of rice, availability of supporting facilities for operation and maintenance, damage rate of drainage system, damage rate of secondary canals and damage rate of primary canals. The total cropping intensity shows a negative relationship to the performance of irrigation systems in semi-arid areas which water is limited. Meanwhile, the area of irrigation scheme, rice productivity, level of the participation of water user association, availability of supporting facilities for operation and maintenance, ratio of the number of operation and maintenance officers to irrigation area, frequency of maintenance of infrastructures, operation and maintenance costs, rehabilitation costs, authority of provincial irrigation areas show a positive relationship to system performance irrigation.